Alveolar Bone Regeneration around Immediate Implants Using an Injectable nHAC/CSH Loaded with Autogenic Blood‐Acquired Mesenchymal Progenitor Cells: An Experimental Study in the Dog Mandible. (11th July 2011) - Han, Xue; Liu, Hongchen; Wang, Dongsheng; Su, Fang; Zhang, Yong; Zhou, Wei; Li, Shujun; Yang, Rui
ABSTRACT Background: Lack of osseointegration between a dental implant and the walls of the alveolar bone is a common problem in immediate implantation. Injectable tissue‐engineered bone (ITB) may be an effective and minimally invasive solution to the problem. In this study, an injectable bone cement, nHAC/CSH, which consists of nano‐hydroxyapatite/collagen (nHAC) and calcium sulfate hemihydrate (CaSO4.½H2O; CSH) was investigated as a tissue‐engineered scaffold material with blood‐acquired mesenchymal progenitor cells (BMPC) as seeding cells. Purpose: The aim of the study was to assess the new bone formation around immediate dental implants using nHAC/CSH loaded with dog blood‐acquired mesenchymal progenitor cells (dBMPC) in a canine model. Materials and Methods: dBMPC were first isolated from peripheral blood of healthy adult dogs. Alizarin red and oil red O staining were then used to evaluate the potential of dBMPC to differentiate into bi‐lineage mesenchymal tissues in vitro. Four healthy mongrel dogs were used in this study. The alveolar bone defects around immediate implants of dogs were created. Each defect was randomly assigned to one of the following three groups: (1) the ITB group (dBMPC + nHAC/CSH); (2) injectable bone cement nHAC/CSH; or (3) no materials (controls). Methylene blue staining was used to examine the bone formation after 3 months. Results: Studies in vitro revealed that dBMPC could be induced to osteoblasts and adipocytes. The ITB group (dBMPC + nHAC/CSH) showed significantly more bone‐implant contact and bone density than either nHAC/CSH or control groups in the areas with peri‐implant defects 3 months after implantation. Conclusion: The results indicate that the ITB composed of nHAC/CSH and dBMPC may represent a useful strategy for the clinical reconstruction of bone defects around immediate implantation. However, further investigation is needed involving the use of human BMPC as well as possible use of stem cells.